Fixed Frequency Sliding Mode – PI Control for Single Phase Unipolar Inverters - John Wiselin, M. C; Rahiman, Riyaz.A. (Asian Journal of Electrical Sciences, 2013)
Sliding Mode – PI controller is recognized as robust controller with a high stability in a wide range of operating conditions, although it suffers from chattering problem. In addition, it cannot be directly applied to multi switches power converters. This paper concerns a sliding controller design with the proportional-integral (PI) control form. First, a theoretical analysis of the considered sliding PI controller is provided. Our analysis reveals that the proportional control term of the sliding PI controller, i.e., sliding proportional controller, can reduce the chattering problem and thus, the robustness can be established. Second, the chattering problem is eliminated by smoothing the control law in a narrow boundary layer, and a pulse width modulator produces the fixed frequency switching law for the inverter. The smoothing procedure is based on limitation of pulse width modulator. Therefore, the chattering problem of the proportional gain is resolved and the valuable robust control property of the sliding integral controller is illustrated again. The simulation model has been developed and tested using MATLAB software.